2022
DOI: 10.1155/2022/6275136
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Regulates Th17/Treg Balance in Treating Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD), also known as chronic nonspecific inflammatory disease of the colon and rectum, is primarily characterized by mucopurulent bloody stools, diarrhea, abdominal pain, and tenesmus. Its cause is uncertain. IBD patients frequently experience a high rate of recurrence, a protracted treatment course, and a high risk of carcinogenesis. Additionally, the difficulty of treatment is significantly increased by these illness characteristics. Currently, the normal treatment for this illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…20,21 Owing to the incurable other hand, TCM has an important role in preventing and treating IBD that effectively alleviate symptoms, improve immunity, and curb progression of the disease. 23 TCM has unique advantages of having low adverse effects and stable efficacy in the overall treatment and maintenance phases of IBD. For example, the isolated rutaecarpine (RUT), a COX-2 inhibitor isolated from Evodia rutaecarpa, could improve dextran sodium sulfate (DSS)-induced IBD and inhibited oxidative stress.…”
Section: Keyword Analysismentioning
confidence: 99%
“…20,21 Owing to the incurable other hand, TCM has an important role in preventing and treating IBD that effectively alleviate symptoms, improve immunity, and curb progression of the disease. 23 TCM has unique advantages of having low adverse effects and stable efficacy in the overall treatment and maintenance phases of IBD. For example, the isolated rutaecarpine (RUT), a COX-2 inhibitor isolated from Evodia rutaecarpa, could improve dextran sodium sulfate (DSS)-induced IBD and inhibited oxidative stress.…”
Section: Keyword Analysismentioning
confidence: 99%
“…The components of medicine food homology (MFH) are complex and can treat intestinal diseases by exerting anti-inflammatory and antioxidant effects, as well as regulating the intestinal flora [ 315 ]. In addition, a growing body of research has demonstrated that TCM has great potential in treating intestinal diseases by regulating intestinal immunity and inflammation through the AHR pathway [ 316 ]. Eating MFH will have a beneficial effect on intestinal health.…”
Section: Dietary Habits Affect Intestinal Health Through Ahrmentioning
confidence: 99%
“…At the same time, the body produces large amounts of cytokines, proteolytic enzymes, and free radicals, which eventually lead to inflammation and ulcers [1,2]. According to a study in the United States, IBD is listed as the fifth most expensive gastrointestinal disease, and its patients accumulate additional Molecules 2024, 29, 379 2 of 27 out-of-pocket costs of nearly $500 million per year in treatment [3]. The treatment of this disease is not ideal due to the lack of medicine with enough efficiency and efficacy, although recent studies have made significant progress in understanding the pathogenesis of IBD.…”
Section: Introductionmentioning
confidence: 99%